Social networks and their relevance to children’s mental health from the perspective of mothers - Al-Rehden, Ghaida Saud (Journal of Educational and Psychological Sciences, 2025)
This study investigates children’s social network preferences and usage patterns and whether there is a correlation between social networks and children’s mental health. The study employed a descriptive approach and a questionnaire tool to collect data. Research focuses on 657 mothers of kindergarten children aged 5–6 years in Hafr Al-Batin. The mothers were randomly chosen since the study found that YouTube is one of the most popular social media platforms among children since it is free, accessible, and does not require downloading videos. The findings revealed that children use social media the most at night, when they are most by themselves. The study found no statistically significant differences between the child’s gender or social networks in relation to the child’s mental health. According to the study, there are statistically significant differences between social networks and the mother’s age, education, and mental health. The results led to the creation of a series of recommendations, which included a particular application for mothers in regards to the detrimental use of social networks. The researcher proposed a variety of ideas, including developing a social networking awareness curriculum, the correct way of using social networking, and incorporating the curriculum into all educational stages.